Interaksi Antara Sesama Warga Binaan Di Rutan Kelas II B Enrekang Kabupaten Enrekang - Nur, Hasruddin (Phinisi Integration Review, 2018)
This research aims at (i) to determine the interactions that occur in detention Enrekang and (ii) guidance system that were made by the inmates in prison Class II B Enrekang. Type of study used in this study is a qualitative research. Subject of the study consisted of (i) the inmates, (ii) Prison officers and (iii) community. In this research, using the technique of sampling with purposive sampling method. Mechanical determination of informants consisting of of inmates who had almost finished his incarceration, inmates are trusted and given responsibility by the officials Prison, the heads of employees crease class II B Enrekang, People who are in the neighborhood of former prisoners. Data collection techniques in this study, observation, interviews and documentation. The validity of this research data is through triangulation and member checks. data analysis techniques in the study include data reduction, data presentation, and conclusion. These results indicate that the interaction of inmates that exists in the crease class II B EnrekangEnrekang , fueled by three factors, namely, factors imitation, suggestion, sympathy, and empathy. In coaching system that occurs in the crease class II B Enrekang district includes development of moral education and fostering creativity